Co-digestion of Rhodosporidium toruloides biorefinery wastes for biogas production - Batista, Ana Paula (2018)
ABSTRACT: Rhodosporiodum toruloides NCYC 921 yeast biorefinery is able to simultaneously provide a gaseous energy carrier, lipids and high-value carotenoids, either using glucose or carob pulp syrup as carbon source in the cultivation step for biomass production. The resulting leftover materials from the yeast biorefinery (YR- de-oiled yeast biomass residue, GS- glucose supernatant, CS- carob supernatant and CR- carob residue) were valued through anaerobic digestion in different mixtures, according to the generated effluents volume. Biogas productions of 55, 31 and 29 mL and methane yield of 236, 179 and 144 mL CH4/g substrate volatile solids (VS) were recorded for the studied mixtures MIX I (YR + GS), MIX II (YR + CS) and MIX III (YR + CS + CR) respectively. The comparison between the biogas production and volatile solids removal obtained for the individual substrates and for the admixtures substrates digestions revealed that co-digestion favoured the conversion of the biorefinery wastes into biogas/methane. Flow cytometry analysis of cells stained with propidium iodide revealed that the proportion of cells with injured membrane was lower in the substrate mixtures digestions than in the individual waste digestions, indicating that co-digestion mitigates the negative effect of potential toxic compounds present in the wastes or produced during the process digestion on the microbial consortium.